PELAKSANAAN PROGRAM PENGUATAN INFRASTRUKTUR PEDESAAN DI DESA SEBANGAR KECAMATAN MANDAU KABUPATEN BENGKALIS TAHUN 2012-2013 - M.Reski Ikhwan; H. Muhammad Ridwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
PPIP is a community-based program. Community empowerment is done so that the results of the implementation of development can be tailored to needs that have been identified in a participatory manner. PPIP strive to create and improve the quality of people's lives, both individually and in groups through participation in solving the existing problems related to poverty and underdevelopment of the village as an effort to improve the quality of life, independence and well-being of society.This study aimed to gain an overview and analysis of the implementation of the PPIP program by village officials and village community Sebangar Mandau sub Bengkalis years 2012-2013 were evaluated from the task and clear goals that accurately reflect the intent of the policy, management plans that allocate tasks and performance standards to implementing organizations, implementing organizational performance measurement which assessed with the goal to be achieved, the control and management system constraints encountered during the implementation process .This study used a qualitative approach with descriptive type that generates data in the form of words written or spoken of people and behaviors that can be observed. Data collected through, documentation and interviews.Based on the research results that the PPIP program implementation in the village Sebangar Mandau sub Bengkalis years 2012-2013 is not implemented effectively. This is because in practice there are problems such as the management plan implemented through village meetings have not been good enough, society is not yet fully participate actively participate in village meetings were held. In addition, control management system for physical control of infrastructure is not good enough, it is dikarenkan intensity insufficient monitoring conducted maximal.Keywords : Implementation, Program PPIP